1993
DOI: 10.1007/bf00374960
|View full text |Cite
|
Sign up to set email alerts
|

Urea derivatives as tools for studying the urea-facilitated transport system

Abstract: The effects of urea structural analogues on the urea-facilitated diffusion system were examined in human red cell membranes (pink ghosts) and in antidiuretic hormone(ADH)-stimulated frog urinary bladder epithelia. In both tissues, urea permeability (P(urea)) was dramatically but reversibly inhibited by a number of urea analogues, such as 1-(3,4-dichlorophenyl)-2-thiourea (DCPTU). This urea derivative reduced the urea flux in a dose-dependent manner (90% inhibition of P(urea) at 0.5 mM concentration of DCPTU). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In BBMVs from the dorsal section, the urea analogue NPTU (80·µmol·l -1 ) significantly reduced urea uptake. This reduction is comparable to that seen in the frog urinary bladder (IC50=79.4·µmol·l -1 ; Martial et al, 1993), indicating a high specificity for this analogue. In the ventral section, acetamide elevated urea uptake above that of the ventral control and the dorsal BBMV in the presence of acetamide.…”
Section: Characteristics Of Urea Transportsupporting
confidence: 74%
“…In BBMVs from the dorsal section, the urea analogue NPTU (80·µmol·l -1 ) significantly reduced urea uptake. This reduction is comparable to that seen in the frog urinary bladder (IC50=79.4·µmol·l -1 ; Martial et al, 1993), indicating a high specificity for this analogue. In the ventral section, acetamide elevated urea uptake above that of the ventral control and the dorsal BBMV in the presence of acetamide.…”
Section: Characteristics Of Urea Transportsupporting
confidence: 74%
“…We chose a somewhat lower concentration of DCPTU (0.25 mmol 1-) as the affinity of DCPTU for the urea transporter is known to be relatively high, for example, DCPTU has an inhibition constant (K I ) of 0.01 mmol -in red cell membranes (Mayrand and Levitt 1983). Although urea analogs, phloretin and DCPTU have not been used in aquatic experiments in previous studies, their effects on urea transport in isolated tissues have been shown to be reversible (Chou and Knepper 1989;Martial et al 1993). Jneturea, °Uturea, and Jnetamm were measured in an initial 2h control flux, a 2h experimental period (urea analogs (5.0 mmol N 1-1) i.e., similar to internal urea levels) or inhibitors (0.25 mmol 1-)), and a final 2h recovery period.…”
Section: Experimental Protocolmentioning
confidence: 98%
“…Phloretin (0.25 mmol 1-) blocks facilitated urea transport in mammalian red blood cells and kidney tubules (e.g., Brahm 1983;Chou and Knepper 1989). The inhibitor, DCPTU (0.5 mmol 1-) has been shown to reversibly inhibit urea flux in frog urinary bladder epithelia (Martial et al 1993). We chose a somewhat lower concentration of DCPTU (0.25 mmol 1-) as the affinity of DCPTU for the urea transporter is known to be relatively high, for example, DCPTU has an inhibition constant (K I ) of 0.01 mmol -in red cell membranes (Mayrand and Levitt 1983).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The control sample was tested as described in Martial et al [16]. For ureaefflux inhibition experiments, 250 pl of anti-Jk3 serum was added to 5 ml ghost suspension (108vesicles/ml).…”
Section: Preparation Of Pink Ghosts and Urea-efflux Measurementsmentioning
confidence: 99%